Efisiensi Pendataran Memori pada Komputasi Matriks Padat: Studi Komparatif Rust dan Go - Hamdan Yuwafi Mastu Wijaya; Ani Dijah Rahajoe; Retno Mumpuni (Jurnal Ilmiah Teknik Informatika (TEKINFO), 2026)
Modern high-performance computing (HPC) demands face the Memory Wall, wherememory layout efficiency is now more crucial in determining performance than the numberof processor cores. Nested dynamic array structures inherently induce pointer chasing,which breaks hardware-level data locality. This paper presents an architectural comparativestudy between the concurrency models of Go (M:N scheduling) and Rust (1:1 kernelthreads) through the evaluation of intensive matrix computations on the order of 500x500to 2000x2000. Experiments contrast conventional nested memory structures against a flatlinear layout (1D Contiguous Memory Layout). Empirical results from isolated tests showthat Go's native implementation dominates in efficiency at medium scales due to its lowGoroutine initiation overhead. However, in Rust, nested structures induce exponentiallatency spikes due to high cache miss metrics. Memory flattening in Rust has been shownjournals.upi-yai.ac.id/index.php/TEKINFO/issue/archiveP-ISSN: 1411-3635E-ISSN: 2962-5645TEKINFO VOL. 27, NO. 2, Oktober 2026 1to eliminate pointer chasing, reduce computational latency by up to 32.3% at the highestorder, and trigger the activation of automatic vectorization (SIMD) instructions by theLLVM compiler. In contrast, manual application of linear index transformations in Goactually creates a massive performance degradation of 79% due to the accumulatedarithmetic calculation load that the runtime fails to optimize. This research demonstratesthat there is no absolute language superiority; architecture selection should be based on thealignment of Data-Oriented Design with compiler capabilities, providing concreterecommendation parameters for designing industrial-scale software systems.